PTSD is associated with an increase in aged T cell phenotypes in adults living in Detroit. (May 2016) - Aiello, Allison E.; Dowd, Jennifer B.; Jayabalasingham, Bamini; Feinstein, Lydia; Uddin, Monica; Simanek, Amanda M.; Cheng, Caroline K.; Galea, Sandro; Wildman, Derek E.; Koenen, Karestan; Pawelec, Graham
Highlights: We examined the association between PTSD and T cell markers of aging. Data were derived from a population-based study of adults aged 18 or older. PTSD was associated with variations in the CD8+ T cell population and CD4:CD8 ratio. Our results suggest that exposure to PTSD may influence immunological aging. Abstract: Background: Psychosocial stress is thought to play a key role in the acceleration of immunological aging. This study investigated the relationship between lifetime and past-year history of post-traumatic stress disorder (PTSD) and the distribution of T cell phenotypes thought to be characteristic of immunological aging. Methods: Data were from 85 individuals who participated in the community-based Detroit Neighborhood Health Study. Immune markers assessed included the CD4:CD8 ratio, the ratio of late-differentiated effector (CCR7-CD45RA+CD27-CD28-) to naïve (CCR7+CD45RA+CD27+CD28+) T cells, the percentage of KLRG1-expressing cells, and the percentage of CD57-expressing cells. Results: In models adjusted for age, gender, race/ethnicity, education, smoking status, and medication use, we found that past-year PTSD was associated with statistically significant differences in the CD8+ T cell population, including a higher ratio of late-differentiated effector to naïve T cells, a higher percentage of KLRG1+ cells, and a higher percentage of CD57+ cells. The percentage of CD57+ cells in the CD4 subset was also significantly higher and the CD4:CD8 ratio significantly lower among individuals who had experienced past-year PTSD. Lifetime PTSD was also associated with differences in several parameters of immune aging. Conclusions: PTSD is associated with an aged immune phenotype and should be evaluated as a potential catalyzer of accelerated immunological aging in future studies.